Exchange rates and the speed of economic recovery: The role of financial development - Boris Fisera (Charles University in Prague, Institute of Economic Studies (IES), 2022)
We study the influence of the exchange rate on the speed of economic recovery in a sample of 67 developed and developing economies over the years 1989-2019. First, using a cross-sectional sample of 341 economic recoveries, we study the effect of nominal depreciation and real undervaluation on the length of economic recovery. Our findings indicate that both nominal depreciation and real undervaluation increase the speed of economic recovery. However, this finding only holds for smaller depreciations/ undervaluations. Second, we use an interacted panel VAR (IPVAR) model to investigate the effect of real undervaluation on the speed of economic recovery after external shock. While we once again find evidence that undervalued domestic currency increases the speed of economic recovery, its positive effect seems limited in size. Furthermore, we also explore the role of financial development in influencing the effectiveness of undervalued domestic currency in stimulating the economic recovery. We find that the higher level of financial development seems to limit the negative effect of an overvalued currency on the speed of economic recovery, but not to influence the effect of an undervalued currency on economic recovery.
Keywords: F10; F30; F31; F43; 330; Economic recovery; exchange rate; currency depreciation; realundervaluation; financial development; interacted panel VAR (IPVAR)